Effects of hydrolyzed yeast on growth performance, intestinal redox homeostasis, and woody breast myopathy in heat-stressed broilers - Al-Abdullatif, Abdulaziz A.; Alhotan, Rashed A.; Al-Badwi, Mohammed A.; Dong, Xinyang; Kettunen, Hannele; Vuorenmaa, Juhani; Sakr, Shimaa A.; Azzam, Mahmoud M. (Frontiers in Veterinary Science, 2024)
The objective of this study was to enhance the knowledge about the effects of hydrolyzed yeast supplementation on growth performance, woody breast myopathy, and its mechanism on intestinal homeostasis using antioxidant and immunomodulatory-related gene expressions in heat-stressed broiler chickens. In a 35-d feeding experiment, 160-day-old male Ross 308 broiler chickens were assigned to four dietary groups, consisting of eight replicates and five birds per replicate. Experimental diets contained four levels of hydrolyzed yeast (HY) (0, 400, 800, or 1,200 mg.kg−1) derived from Saccharomyces cerevisiae. On d 25, birds were exposed to cyclic heat stress (HS) (35°C for 8 h/d from 8 a.m. to 4.00 p.m.) for 10 days. Adding HY at 800 mg.kg−1 numerically decreased the feed conversion ratio (FCR) on days 25–35 (heat stress period) by 2.50%. Furthermore, the addition of HY reduced (P = 0.005) mortality rate compared with those of birds fed the control diet. Supplementation of HY exhibited efficacy (P = 0.09) in diminishing woody breast (WB) in terms of incidence and degree of severity. Furthermore, the added HY decreased (P < 0.001) drip loss values of the Pectoralis major compared with the control diet group; the addition of HY at 400 and 1,200 mg.kg−1 decreased (P < 0.001) cooking loss values in the Pectoralis major. In addition, HY supplementation at 800 mg.kg−1 decreased (P = 0.04) the duodenal mRNA expression of the avian β-defensin 10 (AvBD10) and increased (P < 0.05) the mRNA expression of nuclear factor erythroid 2–related factor 2 (Nrf2), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and secreted immunoglobulin A (sIgA). The addition of HY at 400 and 800 mg.kg−1 decreased (P = 0.001) the duodenal mRNA expression of copper and zinc superoxide dismutase (Cu-ZnSOD1). HY supplementation tended to decrease (P =0.07) the duodenal mRNA expression of heat shock protein 70 (HSP70). The results suggest that hydrolyzed yeast supplementation to broiler chickens exposed to heat stress might improve intestinal redox homeostasis and decrease the mortality rate. The inclusion of 800 mg.kg−1 HY in the diet enhanced duodenal redox homeostasis, while 400–1,200 mg.kg−1 HY reduced mortality rate and exhibited lower drip loss values and reduced woody breast of Pectoralis major in terms of incidence and degree of severity.